Resistência à força de compressão e análise de raio X das sementes de algodão - Martins, Myllena Teixeira (2019)
Cotton is one of the main growing crops in Brazil and in the world, so we continually seek to increase productivity and improve fiber quality. The parameters of fiber quality are affected by the presence of contaminants, especially the seed coat fragments (SCF) that cause great problems in the textile industry during the spinning and dyeing of the fabric. SCFs are parts of seed coatings that have been broken off from the surface of mature or immature seeds during mechanical processing. There are few studies that indicate the possible causes of the origin of these contaminants, being it can be genetic or due to the mechanical processes. The objective of this study was to correlate the compression force with the x-ray analyzes of cotton seeds. The cotton varieties used were: FM 940 GLT, IMA 7201 B2RF, IMA 6501 B2RF, TMG 47 B2RF, IMA 2140, IMA 2129, IMA 7501 WS, and FM 975 WS. The compression test was carried out in the electrotechnical laboratory of the Federal University of Rondonópolis, with the aid of a universal testing machine. For this, each sample remained for 7 days inside a BOD with relative humidity at 65% ± 2 and temperature at 20 ° C ± 1. During the compression test, the seeds were placed horizontally between parallel plates and each seed was analyzed individually. The force and strain data were obtained through the break point of the curve formed during the test. Then, radiographic images of the cotton seeds were produced by the X-ray equipment LX-60 of the Faxitron X-Ray Corporation in the Laboratory of Seed Analysis of the Federal Goiano-Rio Verde Institute. Afterwards, the images were analyzed in the Tomato Analyzer and ImageJ software to verify the free space between the integument and the area containing the embryonic and cotyledon axis and to measure the thickness of the integument, respectively. The experimental design was completely random, with eight treatments and four replicates of 25 seeds, totaling 32 plots. The results were submitted to analysis of variance, and the means comparison was done by the Scott-Knott test at 5% of probability using the SISVAR program and finally the Pearson correlation was applied between the analyzed variables. It was concluded that there was a positive correlation between the rupture force and the thickness of the seed coat and between the density and the free area inside the seeds. Thus, seeds with thicker tegument are more resistant to fragmentation and the density is associated with the quality and volume of the seeds and consequently with their internal filling that is determined according to the degree of development of the embryonic axis and cotyledon.